Development of an Instructional Module on Professional Foundations for the Bachelor of Nursing Science (for Graduates with a Bachelor's Degree in Another Field) - Suwanampa, Thitiphorn; Mahavijit, Pongsatorn; Koolsriroj, Udomluk (Journal of Nursing and Public Health Research, 2025)
This research and development study aimed to explore and analyze learning problems among students enrolled in the Bachelor of Nursing Science Program (for graduates from other fields) in order to develop and evaluate an online instructional module on professional foundations. The sample consisted of nursing instructors responsible for teaching the basic professional practice course, curriculum coordinators of the Bachelor of Nursing Science Program (for graduates from other fields), and students in the program, including 6 third-year students, 6 second-year students, and 40 first-year students. The research instruments included: 1) an interview guide, 2) a professional foundation instructional module comprising 11 modules in the course "Introduction to Human Anatomy and Physiology," 3) a module quality assessment form, 4) pre- and post-tests to measure professional foundational knowledge, and 5) a satisfaction questionnaire. Qualitative data were analyzed using content analysis, while quantitative data were analyzed using descriptive statistics and a dependent samples t-test. The research findings were divided into three phases. In Phase 1, which focused on analyzing students' learning problems, two key issues were identified: 1) the content of the "Introduction to Human Anatomy and Physiology" course was difficult for students to understand, and 2) students experienced high levels of stress while studying this subject. In Phase 2, the development of the online professional foundation instructional module was found to be effective, meeting the standard criterion of 75/75. In Phase 3, after implementing the module, students demonstrated significantly higher post-test knowledge scores compared to pre-test scores, with statistical significance at the 0.01 level, and reported the highest level of satisfaction. Therefore, the use of the online professional foundation instructional module enhanced accessibility to the learning content. However, to further improve learning outcomes, it is recommended that the online module be complemented with hands-on laboratory sessions.